Sociological jurisprudence and legal philosophy - Agrawal, K. B. (ed.); Raizada, R. K. (ed.) (Jaipur, 1993)
In India, there is no good literature on Sociological Jurisprudence and Legal Philosophy. Jurisprudence, philosophy, political science and sociology are intimately related to one another. There is, moreover, an in creasing internationalisation of approach to the subject at present. No attempt, however, has over been made to bring out a book which could show an inter-disciplinary and universal approach to the subject. In this unique work, an attempt has been made to show a cross-section of the work done on sociological jurisprudence and legal philosophy by the scholars of several countries. The book contains valuable thoughts of world-renowned eminent modern jurists and distinguished philosophers, especially from western and third world countries. It will be of immense value to our readers who do not get an opportunity to read such a literature at one place. The book may serve as a do-it-yourself kit for the students of law, philosophy, political and social theory. It would prove to be an aid to all those who are interested in legal philosophy and social philosophy as intellectual pursuits.
Keywords: Jurisprudence